5x+13=2x+6

Simple and best practice solution for 5x+13=2x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+13=2x+6 equation:



5x+13=2x+6
We move all terms to the left:
5x+13-(2x+6)=0
We get rid of parentheses
5x-2x-6+13=0
We add all the numbers together, and all the variables
3x+7=0
We move all terms containing x to the left, all other terms to the right
3x=-7
x=-7/3
x=-2+1/3

See similar equations:

| 15=42-3f | | 3(d+3)=24 | | (x+6)/2+(x+3)/3=14 | | 3(x-1)-x+2=5 | | 38-14=44–x | | 35-4b=11 | | 2n-6=13 | | 2(3s+8)=82 | | 4z/9+2=4 | | (4z)/9+2=4 | | 3,5x+7=7x | | 45=19+b | | z/10=5=7 | | 3(5x+5)=6(9x+5)-93 | | -10(s+5)=-57 | | 3*(3/y)=(9/4) | | D=16a | | 9w=330 | | 5x–2=x+10 | | 3x-3=11-35 | | (5x+75)(-2x–24)=0 | | 77=2a+72 | | 7-x/12=-9 | | 7+x=5 | | -2x-8+(-4-4x)=6+2*7 | | 126=3x–9 | | x+2x(100)+4x(200)=3500 | | 5x+3/3=11 | | 5/9(26-32)=x | | 0.08=x*0.05+(1-x)*0.124 | | -77=-5x+8 | | 6(1=2x)=5(3x-1)-4 |

Equations solver categories